Novosphingobium aureum sp. nov., a marine bacterium isolated from salt flat sediment. Issue 7 (30th July 2021) - Yoo, Yeonjae; Kim, Dongjun; Lee, Hanbyul; Khim, Jong Seong; Kim, Bogun; Yang, Dongmin; Pathiraja, Duleepa; Choi, In-Geol; Kim, Jae-Jin
Abstract : A Gram-stain-negative, aerobic, pale yellow-coloured, rod-shaped marine bacterium designated strain YJ-S2-02 T was isolated from salt flat sediment sampled in Yongyu-do, Republic of Korea. Strain YJ-S2-02 T grew at pH 6.0–9.0 (optimum, pH 7.0), 10–40 °C (optimum, 30 °C) and with optimum 1 % (w/v) NaCl. The 16S rRNA gene sequence analysis indicated that strain YJ-S2-02 T was closely related to Novosphingobium naphthalenivorans NBRC 102051 T (97.8 %) followed by Novosphingobium mathurense SM117 T (97.5 %), Novosphingobium indicum H25 T (97.3 %), Novosphingobium pentaromativorans US6-1 T (96.8 %), Novosphingobium fontis STM-14 T (96.6 %), Novosphingobium endophyticum EGI60015 T (96.5 %), Novosphingobium naphthae D39 T (96.5 %) and Novosphingobium malaysiense MUSC 273 T (95.9 %). The average nucleotide identity and estimated DNA–DNA hybridization values between YJ-S2-02 T and related type strains were 77.0–77.9 % and 19.1–24.0 %. Strain YJ-S2-02 T was characterized as having Q-10 as the predominant respiratory quinone and the principal fatty acids (>10 %) were summed feature 8 (C18 : 1 ω6 c / ω7 c, 20.7 %), C18 : 3 ω 6 c (16.3 %) and C17 : 1 ω 6 c (11.8 %). The polar lipids consisted of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, sphingolipids and two unidentified lipids. The DNA G+C content of strain YJ-S2-02 T was 65.6 mol%. On the basis of the polyphasic taxonomic evidence presented in this study, YJ-S2-02 T should be classified as representing a novel species within the genus Novosphingobium, for which name Novosphingobium aureum is proposed, with the type strain YJ-S2-02 T (=KACC 21677 T =KCTC 72891 T =JCM 33996 T ).